Chinese Herbal Medicine for Osteoporosis: A Systematic Review of Randomized Controlled Trails. (19th September 2012) - Wang, Zhi-qian; Li, Jin-long; Sun, Yue-li; Yao, Min; Gao, Jie; Yang, Zhu; Shi, Qi; Cui, Xue-jun; Wang, Yong-jun
Abstract : Background . Osteoporosis is a major health problem for the elderly population. Chinese herb may be beneficial to osteoporosis due to its capability. Objectives . This study was designed to evaluate the effectiveness of Chinese medicine treatment on the patients with osteoporosis. Search Methods . Randomized controlled trials were retrieved from different 9 databases. Results . This meta analysis included 12 RCTs involving 1816 patients to compare Chinese herbs with placebo or standard anti-osteoporotic therapy in the treatment of bone loss. The pooled data showed that the percent change of increased BMD in the spine is higher with Chinese herb compared to placebo (lumber spine: WMD = 0.07, 95% CI: 0.01–0.04). In the femoral, Chinese herb showed significantly higher increments of BMD compared to placebo (femoral neck: WMD = 0.06, 95% CI: −0.02–0.13). Compared to the other standard anti-osteoporotic drugs, Chinese herbs also show advantage in BMD change (lumber spine: WMD = 0.03, 95% CI: −0.01–0.08; femoral: WMD = 0.01, 95% CI: −0.01–0.02). Conclusions . Our results demonstrated that Chinese herb significantly increased lumbar spine BMD as compared to the placebo or other standard anti-osteoporotic drugs.